Finding Your Introvert/Extrovert Balance in the Workplace. - Bailey-Hughes, Brenda; Kolovou, Tatiana (linkedin.com, 2017)
Balance the introvert and extrovert in you. Grow professionally by learning to cultivate both introverted and extroverted behaviors.